2019
DOI: 10.11591/ijece.v9i5.pp3687-3694
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison between 802.11 and 802.11p for high speed vehicle in VANET

Abstract: <span>Vehicular ad-hoc networks (VANETs) technology has been emerged as a critical research area. Being ad-hoc in nature, VANET is a type of networks that is created from the concept of establishing a network of cars for a specific need or situation. Communication via routing packets over the high-speed vehicles is a challenging task. Vehicles mobility, speed can vary depending on the road specification. However, on highway, the speed can be increase up to 120 – 200 Km/H. Moving at high speed can affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Moving at a high speed can affect the efficiency of the routing, quickly outdating the position information. Therefore, Alwan et al [201] proposed an improvement to the position-based routing mechanisms through the real time estimation of vehicle position and possible changes in the frequency of exchanged data based on the extracted high accuracy position. On the other hand, vehicular traffic congestion is an extremely important challenge that can diminish the effectiveness of underlying communication by causing broadcast storm problems [202].…”
Section: Mobility Parameters Of Vehiclesmentioning
confidence: 99%
“…Moving at a high speed can affect the efficiency of the routing, quickly outdating the position information. Therefore, Alwan et al [201] proposed an improvement to the position-based routing mechanisms through the real time estimation of vehicle position and possible changes in the frequency of exchanged data based on the extracted high accuracy position. On the other hand, vehicular traffic congestion is an extremely important challenge that can diminish the effectiveness of underlying communication by causing broadcast storm problems [202].…”
Section: Mobility Parameters Of Vehiclesmentioning
confidence: 99%
“…Therefore, the MAODV found to be more efficient than the AODV for VANET networks. The AODV and DSR were compared in [37] using PDR, throughput, average end-to-end delay, and jitter. The results showed that the AODV outperforms DSR.…”
Section: Related Workmentioning
confidence: 99%
“…To design an intelligent transport system, it is very important to consider all the major traffic scenarios for simulations. The previous studies focus only on a single environment that only deals with a specific area of ITS, such as in [32], [35], [37], the simulations are performed in a city environment. In [34], a small crossroad is considered for experiments and in [38], a highway is considered for simulations.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…AU and OBU are equipped with vehicles, RSU connected with each other through wired and wireless media. The communication between vehicles is performed through wireless media using dedicated short-range communication (DSRC) protocol identified as IEEE802.11P [1].…”
Section: Introductionmentioning
confidence: 99%